Mathematical Modelling of Auxin Signalling and Transport - Bellows, Simon S (2022)
Background: Auxin, a plant hormone, has been shown to be integrally linked to plant growth. However, due to the small size of auxin molecules it is experimentally difficult to estimate the concentration of auxin within a cell. Therefore, mathematical modelling is a useful tool in testing predictions and understanding auxins behaviour. Two important systems relating to auxin are: auxin transport, the way auxin moves through plant tissue and the patterns it forms; and auxin signalling, the pathway through which auxin affects the activation and repression of genes through auxin sensitive proteins. However, the exact dynamics of auxin transport and auxin signalling remain unclear.